Multifunctional AgNWs@MXene/AgNFs electromagnetic shielding composites for flexible and highly integrated advanced electronics. (10th November 2022) - Qu, Yifei; Li, Xiang; Wang, Xiu; Dai, Hongqi
Abstract: The electromagnetic interference and heat accumulation pose a significant challenge for the traditional high-density single-function electromagnetic shielding materials in advanced flexible integrated electronics. Herein, nano-silver flakes (AgNFs, reflective layer), MXene (Ti3 CNTx, loss layer) and silver nanowires (AgNWs, heat conduction and shielding layer) constructed ordered multi heterogeneous layers high-performance flexible electromagnetic shielding functional composites (AMA composites). Especially the composites exhibited outstanding electromagnetic interference shielding efficiency (EMI SE) of 70.96 dB even with an extremely thin coating of 25 g/m 2, which is 350% higher than that of the commercial standard (20 dB). It is worth noting that the AMA composites also possessed certain qualities such as superior thermal conductivity, flame retardancy, chemical resistance, high-temperature resistance (25 °C–100 °C), and mechanical properties (tensile strength of 44.4 MPa, Young's modulus of 0.6 GPa). The composites display application possibilities in highly integrated advanced flexible electronic products and wearable electronic devices, as well as provide structural design and research ideas for the usage of a new MXene material (Ti3 CNTx) in electromagnetic shielding composite materials. Graphical abstract: Image 1